Menumbuhkan Jiwa Nasionalisme Siswa MI melalui Media Interaktif dalam Pembelajaran PKn - Rabiatun Ummi Rabiah; Misbahul Arifin (Aafiyah: Jurnal Multidisiplin Ilmu, 2025)
Nationalism is one of the core principles that shapes a nation's identity and character, and it should be instilled from an early age. At the elementary level, particularly in Madrasah Ibtidaiyah (MI), Civic Education (PKn) serves as a strategic medium to foster a sense of love for the homeland and pride in being an Indonesian citizen. However, conventional teaching approaches that tend to be one-way and lack active student involvement often make the learning process unengaging and less meaningful for students. Based on a literature review, this article aims to evaluate the role of interactive media in fostering nationalism among MI students. This study employs a literature analysis method, reviewing various sources related to Civic Education and the use of interactive media. The findings indicate that using interactive media such as educational games, instructional videos, digital animations, and other digital platforms can enhance student participation, strengthen understanding of the material, and more effectively instill the values of nationalism. With a more contextual, communicative, and participatory approach, Civic Education can become more engaging, enjoyable, and meaningful for students. Therefore, integrating interactive media into Civic Education at the MI level is highly recommended to support the optimal internalization of national values from an early age.